A new species of Guadua (Poaceae: Bambusoideae: Bambuseae: Guaduinae) from the Colombian Amazon - Londoño, Ximena; Ruiz-Sanchez, Eduardo (Phytotaxa, 2024)
A new species of Guadua, Guadua bambuzoniae Londoño, is described from the Amazon region of Colombia, specifically in the tropical rainforest ecosystem. This species is unusual in that it grows in swampy areas and has several distinct characteristics that differentiate it from all other South American species of Guadua. These include erect and hollow culms at the base, as well as solid and arched culms at the middle and upper portions; primary branches that develop thorns at each culm node; usually a falcated, prominent and fimbriate auricle on the upper part of the culm sheath on one side; elongated and glabrous leaf sheaths; a usually straight, linear-lanceolate pseudospikelet; lemmas pubescent toward the margins with the margins densely ciliated, but otherwise glabrous, and a conspicuous and strong mucron; and paleas only slightly shorter than the lemmas, with broadly winged keels. Here, we provide a geographical distribution map, illustrations, photographs, and a morphological comparison with G. macrospiculata and G. uncinata.